Examining Transformational Leadership as a Mediating Variable in Enhancing Employee Performance - Diana Hasan; Rini Fatma Kartika; Andry Priharta; Hera Oktadiana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study examines how transformational leadership, work motivation, and cohesion influence employee performance in Indonesian Islamic banking institutions. Using survey data from 320 employees at seven Islamic banks and analyzed using PLS-SEM, the results indicate that work motivation and transformational leadership do not directly affect employee performance. However, transformational leadership significantly increases cohesion, which in turn has a strong positive influence on performance. Mediation analysis confirms that cohesion fully mediates the relationship between transformational leadership and employee performance. These findings highlight the importance of collective mechanisms in explaining performance in Sharia-compliant organizations and offer practical insights for Islamic banking leaders.